2021
DOI: 10.3390/pathogens10111400
|View full text |Cite
|
Sign up to set email alerts
|

Identity of Microfilariae Circulating in Dogs from Western and South-Western Romania in the Last Decade

Abstract: Dirofilaria infections in dogs are recognized as widespread mosquito-borne diseases with zoonotic potential, that are caused by the filarioid nematode (Onchocercidae) species Dirofilaria immitis and Dirofilaria repens. The long-term survey conducted in western and south-western Romania was undertaken in order to provide valuable data on the occurrence of Dirofilaria infections in dogs. Blood samples from 1088 dogs, originating from 73 localities of 11 western and south-western counties in Romania, were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the western and south-western regions, Giubega et al [76] reported a prevalence of 9.74%, most of them microfilaremic. In Arges , County (centre/south of the country), the prevalence showed was 6.7% [77]. The highest prevalence was shown in Galati, in the southeast, 42.2% of the studied dogs being infected [78].…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 81%
“…In the western and south-western regions, Giubega et al [76] reported a prevalence of 9.74%, most of them microfilaremic. In Arges , County (centre/south of the country), the prevalence showed was 6.7% [77]. The highest prevalence was shown in Galati, in the southeast, 42.2% of the studied dogs being infected [78].…”
Section: Endemic Areas (■) and Sporadic Cases Reported (■) )mentioning
confidence: 81%
“…The Woo and Knott techniques could generate false-negatives because of low parasitemia, interactions of a single sex of parasites, immaturity of the parasites, ectopic location of the adult worms, and application of microfilaricides, leading to a decrease in the sensitivity of the tests to identify the presence of filariae (46,(48)(49)(50)(51)(52)(53)(54)(55). This is where the identification of antibodies and circulating filarial antigens in blood becomes important (9,16,40,54,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Nationally, a prevalence of up to 60% has been reported for this disease (1,2). Regionally, in western Romania (Timisoara), the current prevalence is approximately 9.74% for heartworm disease (3). Responsible owners often notice a health problem in the dog, with clinical signs of recurrent cough, dyspnea, dark urine, and intolerance to sustained efforts.…”
Section: Introductionmentioning
confidence: 99%